Intellectual disability complicated by sexual addiction: an uncommon presentation of a common condition - Tze, Nicholas Ping Pang; Masiran, Ruziana (BMJ Publishing Group, 2017)
A young man presented with high libido for 3 years, associated with preoccupation with sexual thoughts combined with his pursuit of pornographic materials. He had strong psychological cravings for and had spent large amount of money on sex, resulting in a dispute with his family. There were no mood or psychotic symptoms. Medical history revealed recent diagnosis of gonococcal urethritis. Cognitive assessment showed subtle deficiencies in reasoning and executive functions. There was occasional use of alcohol. Sexual addiction with comorbid mild intellectual disability was diagnosed, and pharmacological as well as psychological management were started.